2007
DOI: 10.1016/j.biombioe.2007.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Farmer willingness to grow switchgrass for energy production

Abstract: Increasing demand for the production of energy from renewable sources has fueled a search for alternatives to supplement those currently in production. One such alternative is switchgrass, a perennial grass native to North America that appears to have considerable potential as a biomass feedstock for energy production. While the properties of switchgrass as a biomass feedstock have been intensively studied, the potential market for switchgrass has received much less attention. A survey of Tennessee farmers was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
116
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(141 citation statements)
references
References 22 publications
19
116
6
Order By: Relevance
“…Unlike traditional crops, most energy crops are new to American farmers. A 2005 survey conducted in Tennessee found that most respondents had not heard of growing switchgrass for biofuel production (Jensen et al 2007). Hence, farmers will need to invest time in order to learn how best to grow these crops.…”
Section: Switching To Perennial Energy Crops Under Uncertainty and Comentioning
confidence: 99%
“…Unlike traditional crops, most energy crops are new to American farmers. A 2005 survey conducted in Tennessee found that most respondents had not heard of growing switchgrass for biofuel production (Jensen et al 2007). Hence, farmers will need to invest time in order to learn how best to grow these crops.…”
Section: Switching To Perennial Energy Crops Under Uncertainty and Comentioning
confidence: 99%
“…As a perennial grass, switchgrass need only be planted once every 10 years or more, but can be harvested annually using conventional hay equipment. In Europe, research on perennial grasses as a crop for bioenergy was focused on Miscanthus but showed some limitations such as its high price for establishment (Casler et al, 2007;Jensen et al, 2007;Cheng, 2009, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The use of energy crops, mainly corn silage, is also widely spread in the farm-scale anaerobic digesters treating manure, to increase the methane yield and the resulting net renewable energy production [5,6]. Panicum vergatum, or switchgrass, is a high yielding (13e18 tonnes(t) ha À1 in Southeastern United States), warm season, perennial grass that can grow more than 2.75 m in height [7]. It was chosen as the model lignocellulosic crop by the US Department of Energy in the 90s and is believed to return 540% more renewable energy than fossil fuel consumption [8], compared to 25% for maize [9].…”
Section: Introductionmentioning
confidence: 99%